Геодезичний моніторинг короткоперіодичних зміщень напірних трубопроводів гідроенергетичних об’єктів (на прикладі Тереблє-Ріцької ГЕС) - Грицюк, Тетяна Юріївна (Національний університет "Львівська політехніка", 2010)
Дисертацію присвячено розробленню теоретичних основ та методики дослідження та визначення короткоперіодичних зміщень напірних трубопроводів гідроенергетичних об’єктів. У дисертації виконано аналіз геодезичного моніторингу за інженерними спорудами ТРГ, експериментально встановлено безпосередню залежність зміни довжин усіх прогонів напірного трубопроводу від зміни рівня води у водосховищі. За результатами добових короткоперіодичних геодезичних вимірів встановлено добовий гармонічний цикл зміщення анкерних опор напірного трубопроводу. З метою визначення та прогнозування остаточних зміщень анкерних опор на кінець доби розроблена методика опрацювання результатів спостережень із застосуванням теорії кінематичних коефіцієнтів і апроксимації спостережень рядом Фур’є. Розроблена методика опрацювання результатів геодезичного моніторингу зміщень анкерних опор напірних трубопроводів у режимі реального часу. Диссертация посвящена разработке теоретических основ и методики исследования короткопериодических смещений напорных трубопроводов гидроэнергетических объектов. В диссертации выполнен анализ геодезического мониторинга за инженерными сооружениями ТРГ, экспериментально установлена непосредственная зависимость изменения длин всех прогонов напорного трубопровода от изменения уровня воды в водохранилище. По результатам суточных короткопериодических геодезических измерений установлен суточный гармоничный цикл смещения анкерных опор напорного трубопровода. С целью определения и прогнозирования окончательных смещений анкерных опор на конец суток, разработана методика обработки результатов наблюдений с применением теории кинематических коэффициентов и аппроксимации наблюдений рядом Фурье. Разработана методика обработки результатов геодезического мониторинга смещений анкерных опор напорных трубопроводов в режиме реального времени. The dissertation is devoted to the theoretical bases and the methods of the investigation and the determination of the short-periodical displacement of support of the penstock HPS. The analyze of the geodetic monitoring for the engineering objects was done. The systematic displacement of support of the penstock HPS was find out. Besides the exploitation of the penstock leaded to the appearance of the slips and free spaces in the zone of the butterfly valve. For the results of the geodetic monitoring of the anchor supports of the penstock Tereblya-Rikska HPS on the planned drainage of the reservoir the direct dependence of the linear deformation all penstock's passes on the variotation of water level in the reservoir was established. For the purpose of study of the influence of short-periodical technologic load on the anchor supports of the penstock the experimental investigation of accuracy of electronic total station Leica TPS 1201 was realized, the theoretical bases and the processing technique of the measurements were developed. The day's harmonic cycle of displacement of the penstock’s anchor supports was established for the results of the daily's short-periodical geodetic measurement. The processing technique of results of supervisions with application of theory of kinematics coefficients and approximations of supervisions by the Fourier series was done. The processing technique of results of the geodetic monitoring of the displacement of support of the penstocks was developed in real-time mode. Develop methods experiments made possible to predict the accumulation of the systematic displacement of the anchor supports and to minimize these displacements.
Геодезический мониторинг короткопериодических смещений напорных трубопроводов гидроэнергетических объектов (на примере Теребле-Рицкой ГЕС)
Geodetic monitoring of the short-periodical displacement of support of the penstock HPS (for example Tereblya-Rikska HPS)
Keywords: the short-periodical displacements; penstock; the systems of the geodetic monitoring; the total station; короткопериодические смещения; напорный трубопровод; системы геодезического мониторинга; роботизированные тахеометры; короткоперіодичні зміщення; напірний трубопровід; системи геодезичного моніторингу; роботизовані тахеометри